Posisi Indonesia di Tengah Fenomena Korporasi Global (Studi Kasus: Relasi Dagang Indonesia – Toyota Pasca Kesepakatan IJEPA) - Aspin Nur Arifin Rivai (Indonesian Perspective, 2017)
This study aims to understand and examine the economic relation between Indonesia and Japan. This paper questioned; how will the degree of Indonesia’s economic dependence on Toyota’s corporation affect the economic diplomacy through IJEPA? As analytical tools, this article used the concept of transnational economic diplomacy. This paper argues that Indonesia has experienced a very high economic dependency phase in the automotive sector, through Toyota Corporation. This dependence is not only on the existing corporation, but also on the partner country - Japan. Meanwhile, amidst the existing dependencies, the IJEPA agreement itself contains a major problem. It is seen that Japan’s offer through MIDEC program in the form of technology transfer has not yet shown its seriousness. As a result, negotiating agreements to implementation is considered a failure. The two findings are alternating to make Indonesia lower in the bargaining position of the next negotiation.Keywords: Transnational economic diplomacy, economic dependency, IJEPA, MIDEC, and Toyota.